2011
DOI: 10.1038/ejhg.2011.208
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation genetic diagnosis in female and male carriers of reciprocal translocations: clinical outcome until delivery of 312 cycles

Abstract: Carriers of reciprocal translocations (rcp) are known to be at risk for reproductive difficulties. Preimplantation genetic diagnosis (PGD) is one of the options these carriers have to try in order to fulfil their desire to have a child. In the present study, we retrospectively looked at the results of 11 years (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007) of PGD for rcp in our center to improve the reproductive counseling of these carriers. During this period 312 cycles were performed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 27 publications
6
23
0
1
Order By: Relevance
“…[39][40][41][42] However, these findings will reduce the number of embryos available for transfer by detecting abnormalities, which may not persist during embryo development, or may be clinically insignificant. The data we present here demonstrate that reciprocal translocation couples are likely to have relatively few normal/balanced embryos; rejecting embryos with apparent 30 Keymolen et al 31 Ko et al 24 Harper et al 6 Outcome measure per cycle Calculated % (95% CI) Calculated % (95% CI) Calculated % (95% CI) Calculated % (95% CI) Calculated % (95% CI)…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…[39][40][41][42] However, these findings will reduce the number of embryos available for transfer by detecting abnormalities, which may not persist during embryo development, or may be clinically insignificant. The data we present here demonstrate that reciprocal translocation couples are likely to have relatively few normal/balanced embryos; rejecting embryos with apparent 30 Keymolen et al 31 Ko et al 24 Harper et al 6 Outcome measure per cycle Calculated % (95% CI) Calculated % (95% CI) Calculated % (95% CI) Calculated % (95% CI) Calculated % (95% CI)…”
Section: Discussionmentioning
confidence: 79%
“…28 Our study also confirms that mosaicism resulting from mitotic anaphase lag is the predominant plausible mechanism. 29 Data from multiple centres carrying out PGD are collected by the ESHRE PGD Consortium; 6 these data for reciprocal translocations and for three large single-centre studies 24,30,31 are shown in Table 3. The overall pregnancy and live birth rates for our couples are slightly higher than in these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Balanced chromosomal translocations are a known cause of RPL [18]. For men with reciprocal chromosomal translocations, pre-implantation genetic screening (PGS) is recommended, as this has increased the live birth rate from 4.9 % to more than 80 % in some studies [19][20][21]. PGS utilizes either FISH or array-based analysis to detect chromosomal abnormalities or genetic defects in embryos undergoing IVF/ICSI [5].…”
Section: Genetic Counselingmentioning
confidence: 99%
“…2 Studies have shown that for couples in whom the male has a reciprocal translocation, 75% of natural pregnancies will result in a spontaneous abortion, with a live birth rate of only 4.9%. 3,4 Increased frequency of male infertility in men with reciprocal translocations is due to abnormal meiosis during spermatogenesis. 5 Abnormal segregation during meiosis can result in sperm with unbalanced translocations (i.e., chromosomal duplications and deletions).…”
Section: Discussionmentioning
confidence: 99%
“…For couples in whom one or more partners have a reciprocal translocation, preimplantation genetic diagnosis (PGD) reduced the frequency of spontaneous abortions to 12.5% and increased the live birth rate to more than 80%. 3,4 Due to the complexity of translocations and the high incidence of chromosomal aneuploidy with similar phenotypes, a review of the existing literature was critical (Table 1). Most patients with chromosomal abnormalities, with the notable exception of patients with 45,X/46,XY including those with complex chromosomal rearrangements, can still achieve pregnancies.…”
Section: Discussionmentioning
confidence: 99%